Progression of rabbit haemorrhagic disease virus 2 upon vaccination in an industrial rabbitry: a laboratorial approach - C.L. Carvalho; E.L. Duarte; J.M. Monteiro; C. Afonso; J. Pacheco; P. Carvalho; P. Mendonça; A. Botelho; T. Albuquerque; P. Themudo; M. Fevereiro; A.M. Henriques; et al. (World Rabbit Science, 2017)
Rabbit haemorrhagic disease virus 2 (RHDV2) emerged recently in several European countries, leading to extensive economic losses in the industry. In response to this new infection, specific inactivated vaccines were developed in Europe and full and rapid setup of protective immunity induced by vaccination was reported. However, data on the efficacy of these vaccines in an ongoing-infection scenario is unavailable. In this study we investigated an infected RHDV2 indoor industrial meat rabbitry, where fatalities continued to occur after the implementation of the RHDV2 vaccination, introduced to control the disease. The aim of this study was to understand if these mortalities were RHDV2-related, to discover if the dead animals showed any common features such as age or time distance from vaccination, and to identify the source of the outbreak. Anatomo-pathological analysis of vaccinated animals with the virus showed lesions compatible with systemic haemorrhagic disease and RHDV2-RNA was detected in 85.7% of the animals tested. Sequencing of the vp60 gene amplified from liver samples led to the recognition of RHDV2 field strains demonstrating that after the implementation of vaccination, RHDV2 continued to circulate in the premises and to cause sporadic deaths. A nearby, semi-intensive, RHDV2 infected farm belonging to the same owner was identified as the most probable source of the virus. The main risk factors for virus introduction in these two industries were identified. Despite the virus being able to infect a few of the vaccinated rabbits, the significant decrease in mortality rate observed in vaccinated adult rabbits clearly reflects the efficacy of the vaccination. Nonetheless, the time taken to control the infection also highlights the importance of RHDV2 vaccination prior to the first contact with the virus, highly recommendable in endemic areas, to mitigate the infection’s impact on the industry.